DESENVOLVIMENTO DE DIFERENTES DISPOSITIVOS ELETROQUÍMICOS A BASE DE OURO APLICADOS COMO SENSORES E BIOSSENSORES - Santos, Cleverson Siqueira (2016)
This thesis describes the preparation, characterization and application of electrochemical sensors and biosensors, using different modification techniques, based on Au as transducer. The enzymatic biosensor applied on the detection of pesticide carbaryl was built on a gold electrode functionalized with a monolayer of polyamidoamine dendrimer of fourth generation with a cystamine core (PAMAM-G4) on which it was immobilized the acetylcholinesterase enzyme (AChE), with the aid of glutaraldehyde. After evaluate and determine the best conditions for immobilization of the AChE enzyme (glutaraldehyde concentration of 1% (v/v) and the concentration of enzyme units 496 U. mL-1) on the monolayer of PAMAM, the catalytic activity of the enzyme was evaluated by chronoamperometry in presence of enzymatic substrate AChI obtaining = 2.9 . −1 . The biosensor response for carbaryl detection was based on the inhibition of the enzymatic activity caused by the pesticide. It was verified that 5 min in the pesticide solution is sufficient to block the enzyme active sites. After determining the best conditions for the construction of the biosensor, it was applied for carbaryl detection in the concentration range from 1.0 to 9.0 mol. L-1. The detection and quantification limits were found to be 0.0108 mol. L-1 and 0.032 mol. L-1, respectively. In the second chapter, it is reported the development of an immunosensor applied to qualitative detection of antibodies (AB) T. cruzi. The sensor was built on gold electrode modified with the thiol 3-mercaptopropionic acid (MPA) and the antigens (AG) T. cruzi were covalently immobilized on this surface by the reaction with EDC and NHS. The influence of concentration and of immersion time in the AG solution were evaluated using the techniques of cyclic voltammetry and electrochemical impedance spectroscopy in presence of [Fe(CN)6]3-/4- and the results showed that the best conditions were immersion time of 15 minutes and AG concentration of 0.5 g. L-1.The possible sites of non-specific binding were blocked with bovine serum albumin (BSA). The immersion time in the solution (AB) was also evaluated and the results showed that 30 minutes are sufficient for all specific bonds sites were occupied by AB T. cruzi. Selectivity tests in the absence of AB, only in the serum sample, and in the presence of AB Toxoplasma were performed. The results demonstrated that the immunosensor is selective, since it presented charge transfer resistance (Rct) values in the presence of AB T. cruzi 70% higher than the Rct values in presence of possible interferences.Therefore, the immunosensor presents itself as an alternative to qualitative diagnosis of american trypanosomiasis. In the third chapter, it is reported the modification of carbon graphite electrodes (CG) obtained from dry batteries zinc/carbon with Au microparticles obtained by potentiostatic electrodeposition. The variables involved in the electrodeposition process, such as the gold salt concentration, time and deposition potential were evaluated and optimized using cyclic voltammetry technique in the presence of redox couple [Fe(CN)6]3-/4-. The best conditions for the Au deposition were electrodeposition time of 700 s, potential of +0.3 V and concentration of 10.0 mmol. L-1. In these conditions, Au spherical particles were obtained with an average size of 420 nm, which were homogeneously deposited on the surface of GC electrode and promoted the increase of the electroactive area (GC electrode showed an area of 0.12 cm2 and GC/Au electrode presented an area of 0.25 cm2). The GC/Au electrode was applied for the separation and quantification of dopamine and uric acid present in a mixture. The voltammetric results showed that the GC/Au sensor is selective, once the potential peak separation between the DA and UA species was 370 mV. The detection and quantification limits were found to be 1.86 mol. L-1 and 6.09 mol. L-1 for dopamine and uric acid 17.5 mol. L-1 and 58.5 mol. L-1, respectively. In the development of the three electrochemical devices gold electrodes were used. From the results obtained for the three developed electrochemical devices it can be concluded that high electric conductivity, chemical stability, biocompatibility, ability to miniaturization in the form of microstructures and ease of functionalization of Au electrodes make them suitable conductive matrixes for construction of electrochemical sensors and particularly biosensors.